PENGUMPULAN DAN PENGELOLAAN ZAKAT, INFAQ DAN SHODAQOH (LAZIS MUHAMMADIYAH LAMONGAN) - Fauzul Mizanul Ahsan; Raditya Sukmana (Universitas Airlangga, 2019)
The duty of collecting and managing zakat, infaq and shodaqoh in a systematic and well-organized way is the main duty of LAZIS Muhammadiyah Lamongan, even though in its implementation it must be supported, since LAZIS Muhammadiyah itself faces considerable challenges when implementing in the field. Seeing this problem, the researcher wanted to photograph the management and collection of zakat funds, infaq and shodaqoh by LAZIS Muhammadiyah Lamongan, whether or not it went well. Based on the results of preliminary observations, there has been a suspicion that there is an impossibility of conducting ZIS funds distribution by LAZIS Muhammadiyah Lamongan, especially at a glance the LAZIS administrators are still focused on improving the LAZIS Muhammadiyah Lamongan building infrastructure in 2018. However, when we see developments in 2019 there is sufficient progress done well. So in this context the researcher wants to photograph the phenomenon that occurred in LAZIS Muhammadiyah Lamongan between 2018 and 2019. The research objective of this phenomenon is for researchers to see what phenomena occur during the year and see the phenomenon of collecting zakat funds, infaq and shodaqoh and how LAZIS management collects and manages ZIS funds to be distributed to those deserve to receive it.Keywords: Zakat, Infaq, Shodaqoh, Collection and Management, Muhammadiyah, LAZIS